Hans-Jochen Vogel. SPD. Freitag, 5.12.1986, 20.00 Uhr, DA-Wixhausen, Bürgerm.-Pohl-Haus - Sozialdemokratische Partei Deutschlands (SPD), Parteivorstand, Bonn; VOD, Heidelberg
Bemerkungen: großflächiges farbiges Fotoportrait Hans-Jochen Vogel